A novel multiplexing data transmission architecture: multiplexing modulator (MM) for twin remote sensing satellites - Zhao, Wenjie; Rao, Jianing; Han, Shuangxue; Jia, Wenyuan; Song, Jingxing; Dong, Wentao; Dong, Zhenxing; Ma, Xiaoyong; Wang, Jing; Xie, Man; Zhu, Yan; An, Junshe (Frontiers in Astronomy and Space Sciences, 2026)
This paper proposes a novel standalone engineering model for space data transmission - the Multiplexing Modulator (MM). In previous space missions, multiplexers and modulators operated as separate standalone units: multiplexers aggregated multiple low-rate signals into single high-rate streams to enhance channel efficiency, while modulators converted baseband signals into high-frequency carrier waves suitable for channel transmission. This paper integrates both functionalities into a unified Multiplexing Modulator (MM), achieving substantial spacecraft electronics consolidation. The integration reduces weight by over 40%, decreases volume by 35% compared to discrete units, and power consumption by over 25%. All while maintaining space-grade reliability. The newly designed MM performs integrated processing of payload and telemetry data through multiplexing, storage, encryption, and X-band modulation before transmitting processed signals to ground stations via phased array antenna. Key innovations include 12Tbit massive storage capacity, multi-mode downlink capabilities, exceptional stability, high radiation tolerance, and ultra-low power consumption.